Development of rubber-based intercropping system in Southern Thailand: Problems and obstacles - Charernjiratragul, Somboon; Romyen, Arisara; Satsue, Palakorn (Kasetsart Journal of Social Sciences, 2017)
The present development and impacts of rubber-based intercropping systems were investigated and the associated problems and obstacles discussed with regard to Kaopra subdistrict, Sonkhla province and Tamod subdistrict, Patalung province. Twenty three key informants were surveyed using in-depth interviews. Two workshops and one seminar were held in the area to gather more information. All data were synthesized using content analysis. The results revealed that the regulations of the Office of Rubber Replanting Aid Fund were relaxed for rubber planters (who requested replanting aid funding) to allow not more than 15 rubber-based intercrop trees in the replanted plot. Rubber-based intercrops generated positive impacts in environmental, economic, and food security dimensions to rubber planters. However, almost all of the rubber planters in the study areas where the planters have substantially practiced the rubber-based intercropping system (RBIS) are still practicing the rubber monocropping system (RMCS). Most of the RBIS practiced by planters were encouraged by the local civic group. The most popular rubber-based intercrops found in the study areas were forest trees, fast growing trees, and fruit trees, respectively. Two main problems and obstacles to the development of the RBIS in Southern Thailand were identified. First, the government agricultural policy mainly emphasized increasing total production under an export-oriented policy, which was consistent with the RMCS. Second, rubber planters (by perception or habit) considered that the RBIS itself was an obstacle to rubber on-farm management. Consequently, the concerned government agencies should actively provide a complete compendium of RBIS knowledge and benefits to the farmers.